Вторая попытка: роман / Даниэла Стил - Стил Даниэла (Эксмо, 2008)
Экземпляры: аб (20190902) / Инвентарный номер: 54375 / Цена: 70.00 / Сис.шифр: И (Амер) / Авт.знак: С 80 / ГРНТИ: 17.82 / ББК: 84(4Сое)